2016
DOI: 10.1016/j.jaapos.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Cataract secondary to self-inflicted blunt trauma in children with autism spectrum disorder

Abstract: We report 3 cases of bilateral cataract secondary to self-inflicted blunt eye trauma in children with autism spectrum disorder (ASD). All 3 children hit their foreheads, orbits, or globes repeatedly for long periods of time and developed cataracts. Clinicians must be aware of this phenomenon to diagnose ocular pathology early and to provide adequate education, counseling, and services to affected patients and their families and to put appropriate postoperative care mechanisms in place to prevent permanent ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Lee et al. 1 also report that retinal detachment is one of the most serious complications of continued SII after the diagnosis of cataract, which was noted bilaterally in two out of three patients in their case series. More recently, reports have suggested that the incidence of retinal detachment in cataracts caused by chronic SII is 24-fold higher than cataracts due to accidental injuries.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Lee et al. 1 also report that retinal detachment is one of the most serious complications of continued SII after the diagnosis of cataract, which was noted bilaterally in two out of three patients in their case series. More recently, reports have suggested that the incidence of retinal detachment in cataracts caused by chronic SII is 24-fold higher than cataracts due to accidental injuries.…”
Section: Discussionmentioning
confidence: 83%
“…Customized management strategies are thus essential for improving the visual prognosis in this patient population. 1 , 2 , 20 Continued hospital admission or a temporary rehabilitation stay may be required due to poor adherence to postoperative care including postoperative administration of drops. In circumstances where hospital admission is not feasible, consideration of postoperative oral medications and ongoing community support services will ensure appropriate recovery and were successfully implemented in majority of our cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ocular self-injury, while uncommon, is an important consideration when evaluating patients with DD, as trauma is a common cause of cataracts [15]. Reports of self-inflicted blunt head trauma as a mechanism for cataract development also correlate with a higher incidence of vitreous hemorrhage, RD, and self-enucleation at presentation in patients with DD [15] [16] [17]. Even without visible injury to the globe or eyelid, dense cataracts have been reported in patients with chronic headbanging behavior [17].…”
Section: Discussionmentioning
confidence: 99%